Applying Convergent Immunity to Innovative Vaccines Targeting Staphylococcus aureus - Yeaman, Michael R.; Filler, Scott G.; Schmidt, Clint S.; Ibrahim, Ashraf S.; Edwards, John E.; Hennessey, John P. (Frontiers in Immunology, 2014)
Recent perspectives forecast a new paradigm for future “3rd generation” vaccines based on commonalities found in diverse pathogens or convergent immune defenses to such pathogens. For Staphylococcus aureus, recurring infections and a limited success of vaccines containing S. aureus antigens imply that native antigens induce immune responses insufficient for optimal efficacy. These perspectives exemplify the need to apply novel vaccine strategies to high priority pathogens. One such approach can be termed convergent immunity, where antigens from non-target organisms that contain epitope homologues found in the target organism are applied in vaccines. This approach aims to evoke atypical immune defenses via synergistic processes that 1) afford protective efficacy; 2) target an epitope from one organism that contributes to protective immunity against another; 3) cross-protect against multiple pathogens occupying a common anatomic or immunologic niche; and/or 4) overcome immune subversion or avoidance strategies of target pathogens. Thus, convergent immunity has a potential to promote protective efficacy not usually elicited by native antigens from a target pathogen. Variations of this concept have been mainstays in the history of viral and bacterial vaccine development. A more far-reaching example is the pre–clinical evidence that specific fungal antigens can induce cross-kingdom protection against bacterial pathogens. This trans-kingdom protection has been demonstrated in preclinical studies of the recombinant Candida albicans agglutinin-like sequence 3 protein (rAls3) where it was shown that a vaccine containing rAls3 provides homologous protection against C. albicans, heterologous protection against several other Candida species, and convergent protection against several strains of S. aureus. Convergent immunity reflects an intriguing new approach to designing and developing vaccine antigens and is considered here in the context of vaccines to target S. aureus.